A Cytotoxic Rocaglate Compound from The Stembark of Aglaia argentea (Meliaceae) - Ace Tatang Hidayat; Kindi Farabi; Desi Harneti; Nurlelasari Nurlelasari; Rani Maharani; Tri Mayanti; Unang Supratman; Yoshihito Shiono (Universitas Jenderal Soedirman, 2017)
The Aglaia genus belong to Meliceae family is unique plant species because the presence of rocaglate and rocaglamide which is so far isolated only from Aglaia genus, indicate that type of this compound as a chemical marker for the genus of Aglaia. This type of compound known to have strong activity, such as insecticide and cytotoxic. This study describe the isolation, structure elucidation, and cytotoxic activity of an isolated rocaglate compound. Dried stembark of A. argentea extracted with methanol and partition between n-hexane, ethyl acetate, and n-butanol, respectively The extracts were tested against P-388 murine leukemia cells and the ethyl acetat showed strongest activity with IC50 value of 15.5 mg/mL. The ethyl acetate then was separated and purified with chromatography technique to obtain isolated compound 1. The chemical structure of isolated compounds were elucidated by spectroscopic methods including one and two-dimensional NMR as well as high-resolution mass spectrometric analysis and identified as a methyl rocaglate. Compound 1 showed strong cytotoxic activity with an IC50 value of < 0.1 μg/mL.